APPLICATION OF INQUIRY LEARNING WITH A FLIPPED CLASSROOM APPROACH TO IMPROVE STUDENTS' SCIENCE PROCESS SKILLS ON DYNAMIC FLUID MATERIALS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2021)
This study aims to obtain an overview of improving students' science process skills by applying inquiry learning with a flipped classroom approach on dynamic fluid materials. This study applies a pre-experimental design using a pretest-posttest control group design. The research subjects were students of class XI in one of the public high schools in Kampar Regency, Riau Province with a sampling technique based on certain considerations (purposive sampling). The sample in this study was one class of XI IPA students which was reopened by 25 students with an average age of 17 years. The research data was obtained through a science process skills test in the form of multiple choice as many as 20 items that have been validated and tested. The results showed that inquiry learning with a flipped classroom approach on dynamic fluid materials can improve science process skills after learning activities with an N-gain of 0.31 are categorized as moderate.
Keywords: inquiry; flipped classroom; science process skills